TARIBAN1, TARIBAN2, TARIBAN3, and TARIBAN4 ‘Matooke’ cooking banana cultivars for the Great Lakes Region of Africa - Madalla, Noel A.; Massawe, Cornel; Mpoki, Shimwela; Mbongo, Daud Batson; Kindimba, Grace; Kubiriba, Jerome; Arinaitwe, Ivan; Nowakunda, Kephas; Namanya, Priver; Tumuhimbise, Robooni; Okurut, Asher Wilson; Saria, Adolf; et al. (American Society for Horticultural Science, 2022)
Bananas and plantains (Musa sp.) are important staple and income-generating fruit crops for millions of people worldwide (Robinson and Saúco 2010; Ssebuliba et al. 2005). They are edible and vegetatively propagated parthenocarpic species (Ortiz 1997; Simmonds 1962). East African highland bananas (EAHBs) are a distinct group of cultivars found only in the highland of African Great Lakes region, where the “greatest mass of bananas in the world” are found (Simmonds 1966). Bananas are important in the food economy of millions of people in this region, with annual per capita consumption estimated to be between 250 and 600 kg (Karamura et al. 2012). These triploid (2n = 3x = 33 chromosomes) cultivars are known locally as Matooke. When fully ripe, they can be eaten raw like dessert bananas; however, because their pulp is insipid, they are mostly eaten after cooking. Shepherd (1957) referred to them as the ‘Lujugira-Mutika’ subgroup of the AAA genome group. They are also known by its acronym (EAHBs) because they thrive on the East African plateau at altitudes ranging from 900 to 1800 m above sea level (Davies 1995). A small group of these EAHBs are processed into a beverage, and called beer or ‘Mbidde’ bananas.